2014
DOI: 10.1007/s00737-014-0459-y
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of postpartum depression in Miyagi, Japan, after the Great East Japan Earthquake

Abstract: This study explores the correlation between the impact of the Great East Japan Earthquake and the incidence of postpartum depression in Miyagi prefecture, Japan. The design used was a cross-sectional study with self-administered questionnaires, 6–9 months after the disaster. The results showed the prevalence of postnatal women with Edinburgh Postnatal Depression Scale (EPDS) score of ≥9 to be 21.3 %. Multivariate analysis showed that exposure to tsunami (odds ratio, 1.80; 95 % confidence interval, 1.16–2.78) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…[7][8][9] The authors previously reported an increased incidence of perinatal depression and psychological distress in areas affected by the Great East Japan Earthquake. [10][11][12][13] Natural disasters destroy social networks and community relationships. This loss of community also results in secondary emotional trauma and depression.…”
mentioning
confidence: 99%
“…[7][8][9] The authors previously reported an increased incidence of perinatal depression and psychological distress in areas affected by the Great East Japan Earthquake. [10][11][12][13] Natural disasters destroy social networks and community relationships. This loss of community also results in secondary emotional trauma and depression.…”
mentioning
confidence: 99%
“…1 Previous studies have suggested that maternal mental health disorders, including perinatal depression, can be influenced by the devastation caused by a natural disaster. [2][3][4][5] Perinatal depression can affect the mental health of postnatal women 6 and may impact the quality of care given to the newborn. 7 Maternal psychosocial health can affect the mother-infant relationship, [8][9][10] the nutritional status of the infants, illness, 11,12 and children's emotional or cognitive problems.…”
mentioning
confidence: 99%
“…The percentage of mothers with depressive symptoms (EPDS ≥ 9) was remarkably higher than that found in normal circumstances in Japan; it was even higher than that after the Great East Japan Earthquake (Nishigori et al 2014). In particular, mothers living in provinces with severe COVID-19 prevalence were at risk.…”
Section: Discussionmentioning
confidence: 75%